A new species of the genus Eterusia Hope from western China (Lepidoptera, Zygaenidae, Chalcosiinae) - Huang, Si-Yao; Zhang, Yu-Long; Horie, Kiyoshi; Espeland, Marianne (Zootaxa, 2023)
A new species Eterusia sinoraja Huang & Horie sp. n. is described from western Sichuan Province, western China. The comparison is made with the reminiscent E. raja Moore, 1859 from northeastern India. The adult and genitalia of both sexes of the aforementioned taxa are illustrated.